A Broad m6A Modification Landscape in Inflammatory Bowel Disease - Nie, Kai; Yi, Jun; Yang, Yuanyuan; Deng, Minzi; Yang, Yan; Wang, Tianyu; Chen, Xuejie; Zhang, Zhaoyu; Wang, Xiaoyan (Frontiers in Cell and Developmental Biology, 2022)
Background and Aims: N6-Methyladenosine (m6A) is the most common post-transcriptional modification on eukaryotic mRNA, affecting the mRNA’s fate. The role of m6A regulation in inflammatory bowel disease is unclear. Here, we investigated the m6A landscape in inflammatory bowel diseases (IBD). Methods: Eleven human IBD microarray datasets were recruited from the Gene Expression Omnibus database and four were selected as discovery cohorts. An RNA-seq dataset from the Inflammatory Bowel Disease Multi’omics Database was used as a validation cohort. m6A regulators were measured in volunteers’ colonic samples. Consensus clustering and immune scoring were used to estimate the characteristics of m6A regulation in IBD. m6A-related characteristics of different sub-phenotypes, sample sources, and biological therapeutic responses were determined using seven independent datasets. Results: m6A modification involves methyltransferases (writers), demethylases (erasers), and methylation-reading proteins (readers). A wide interaction exists between m6A regulators and IBD risk genes. The IBD risk loci can also be modified by m6A modifications in the public m6A sequencing data. Furthermore, m6A regulators displayed extensive differential expression in four independent discovery cohorts that share common differential genes (IGF2BP2, HNRNPA2B1, ZCCHC4, and EIF3I). In the validated cohort and enrolled volunteers’ colonic biopsy samples, the differential m6A regulators were reconfirmed. Two clusters of consensus clustering exhibit different immune phenotypes. m6A-modified positions exist in the core IBD immune cytokines. Another set of IBD datasets revealed m6A-related differences across clinical phenotypes, biological samples, and therapeutic response subgroups in IBD patients. Conclusion: Regulation of m6A methylation is widely involved in IBD occurrence and development. m6A modifications in risk variants, core cytokines, immune cells, and other proteins may deeply influence the pathophysiology and clinical phenotypes. Further studies are needed to determine its role in IBD.